Effects of pH on Grain Size and Structure of ZnO Nanoparticle Synthesized via Sol–Gel Method for Enhanced Thermoelectric Materials - Suraya, Sulaiman; Tuan Muhammad, Tuan Zahrin; Nadhrah, Md Yatim; Mohd Faizul, Mohd Sabri; Mohamad Farid, Mohamad Sharif (Springer Nature Singapore, 2024)
This chapter delves into the critical role of pH in the synthesis of ZnO nanoparticles using the sol–gel method, focusing on how varying pH levels influence grain size, structure, and thermoelectric performance. The study highlights the importance of nanostructuring and doping techniques to enhance the figure of merit (ZT) of ZnO-based thermoelectric materials. Through XRD analysis, the authors confirm the successful synthesis of highly crystalline ZnO nanoparticles with a hexagonal wurtzite structure. FESEM images reveal the impact of pH on the morphology of ZnO nanoparticles, with optimal conditions identified for achieving desirable crystalline structures and morphologies. EDX analysis validates the high purity and stoichiometric composition of the synthesized ZnO nanoparticles. The findings contribute to the development of more efficient thermoelectric materials for waste heat recovery, paving the way for sustainable energy solutions.